Analisis Struktural Prosa Abad 19 “Cerpen : Iblĺsu Yantashiru/Kemenangan Iblis”Karya Dr. Taufiq El-Hakim - Nurul Hidayah; Nur Hanifatus Sholeha (Universitas KH. A. Wahab Hasbullah, 2019)
Story or fairy tale is one of the literary forms which is a human personal expression in the form of experiences, thoughts, feelings, enthusiasm, beliefs in concrete forms that evoke a beautiful charm with language tools. The theory used by researchers to analyze this research is intrinsic theory. The purpose of this study was to find out the elements contained in the short story